The welfare effects of discriminating between in-state and out-of-state students - Malte Hübner (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2009)
This paper considers the decentralized funding of public universities in a federation when students and graduates are mobile. In particular, I discuss whether local governments should be given the right to differentiate tuition fees between in-state and out-of-state students. I develop a model of decentralized decision making which allows me to draw conclusions about how such a price-discrimination affects welfare and the number of students in a federation. It is shown that local governments differentiate fees if allowed to do so and that this reduces the mobility of students and federal welfare. To assess the impact of differentiated fees on the number of students in the federation this paper extends previous work by endogenizing the number of students. The model predicts that when differentiated fees are used less individuals decide to attend university.
Keywords: H42; H72; H71; I22; 330; fiscal federalism; funding of higher education; student mobility; tuition fees; preferential tax regimes